CNS efficacy of afatinib as first-line treatment in advanced non-small cell lung cancer patients with EGFR mutations - Kang, Liping; Mai, Jianliang; Liang, Weiting; Zou, Qihua; Huang, Caiwen; Lin, Yongbin; Liang, Ying (Frontiers in Oncology, 2023)
Abstract Background: Afatinib is a potent, irreversible second-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor which has demonstrated efficacy in advanced non-small cell lung cancer (NSCLC) patients harboring either common or uncommon EGFR mutations. However, data on its activity against brain metastases are limited. This study aimed to retrospectively evaluate the efficacy and safety of afatinib as first-line treatment for EGFR-mutant NSCLC patients with brain metastases. Methods: Treatment-naive advanced NSCLC patients harboring EGFR mutations and brain metastases treated with afatinib were retrospectively reviewed to assess the central nervous system (CNS) efficacy and also the systematic benefits. Results: Totally 43 patients with measurable or non-measurable brain metastases were enrolled in the CNS full analysis (cFAS) set. Among them, 23 patients with measurable brain metastases were included in the CNS evaluable for response (cEFR) set. The CNS ORR was 48.8% (95% CI, 33.3 - 64.5%) in the cFAS set and 82.6% (95% CI, 61.2 - 95.0%) in the cEFR set, respectively. CNS mDoR was 8.9 months (95% CI, 4.7 - 13.1 months) and CNS mPFS was 12.7 months (95% CI, 6.9 - 18.5 months) in the cFAS set. In the subgroup analysis stratified by EGFR mutation types, CNS ORR of cEFR set in the common mutation cohort was 100% (95% CI, 75.3 - 100%) and 60% (95% CI, 26.2 - 87.8%) in the uncommon mutation cohort (p = 0.024); CNS ORR of cFAS set was 57.7% (95% CI, 36.9 - 76.6%) and 35.3% (95% CI, 14.2 - 61.7%), respectively (p = 0.151). CNS mPFS was 14.4 months in patients with common mutations and 6.1 months in patients with uncommon mutations (hazard ratio, 0.47; 95% CI, 0.22 - 1.00; p = 0.045). Patients with common mutations showed a significantly lower cumulative incidence of CNS failure than uncommon mutation cohort (p = 0.0026). Most of patients experienced grade 1/2 treatment-related adverse events. Conclusions: First-line afatinib demonstrated encouraging efficacy on brain metastases in NSCLC patients harboring either common or major uncommon EGFR mutations in a real-world setting, with manageable toxicities. Patients with common mutations showed better CNS outcomes than those with uncommon mutations.